Eksplorasi Natural Adjuvant Vaksin melalui Pendekatan Integratif Identifikasi Lapangan, Meta-Analisis dan Filogenetika - Siti Rukmana; Robi'atul Andawiyah; Fatmawati; Kholifatur Rosyidah; Maslahah; Fadhilah; Alya Firdaus; Akhmad Ferdiansyah (Universitas PGRI Silampari, 2026)
Vaccination remains the primary strategy for controlling infectious diseases, yet the move to highly purified antigens requires the development of effective adjuvants to boost immunogenicity. Synthetic adjuvants often face limitations due to side effects and production costs, creating interest in natural bioactive compounds from local biodiversity. This study aims to explore and map the potential of local plants as sources of vaccine adjuvants using an integrative field-and-bioinformatics approach. Direct field exploration and morphological identification were conducted on 41 local plant species. This was integrated with a systematic meta-analysis of bioactive profiles and phylogenetic analysis to evaluate the evolutionary distribution of adjuvant candidates. The analysis identified 10 different classes of bioactive compounds across the surveyed flora. Flavonoids appeared as the most common type found in 20 species, followed by alkaloids which found in 6 species, while terpenoids, triterpenoids, and phenolics were respectively identified in 3 species. Other identified compounds included tannins, saponins, iso-flavonoids, steroids, and naphthoquinones. Phylogenetic mapping revealed that these potential adjuvants are distributed across 23 botanical families, showing that these local plants have evolved to posses diverse immune-boosting compounds. The diversity of bioactive compounds, particularly the predominance of flavonoids, highlights the significant potential of local flora for future vaccine formulation. Utilizing these indigenous resources can enhance local vaccine production capabilities and improve global vaccine accessibility.